Transgenerational Plasticity and Bet-Hedging: A Framework for Reaction Norm Evolution - Joschinski, Jens; Bonte, Dries (Frontiers in Ecology and Evolution, 2020)
Decision-making under uncertain conditions favors bet-hedging (avoidance of fitness variance), whereas predictable environments favor phenotypic plasticity. However, entirely predictable or entirely unpredictable conditions are rarely found in nature. Intermediate strategies are required when the time lag between information sensing and phenotype induction is large (e.g. transgenerational plasticity) and when cues are only partially predictive of future conditions. Nevertheless, current theory regards plasticity and bet-hedging as distinct entities. We here develop a unifying framework: based on traits with binary outcomes like seed germination or diapause incidence we clarify that diversified bet-hedging (risk-spreading among one’s offspring) and transgenerational plasticity are mutually exclusive strategies, arising from opposing changes in reaction norms (allocating phenotypic variance among or within environments). We further explain the relationship of this continuum with arithmetic mean maximization vs. conservative bet-hedging (a risk-avoidance strategy), and canalization vs. phenotypic variance in a three-dimensional continuum of reaction norm evolution. We discuss under which scenarios costs and limits may constrain the evolution of reaction norm shapes.